Reduction in DALYs lost due to soil-transmitted helminthiases and schistosomiasis from 2000 to 2019 is parallel to the increase in coverage of the global control programmes. - Antonio Montresor; Pauline Mwinzi; Denise Mupfasoni; Amadou Garba (PLoS Neglected Tropical Diseases)
Preventive chemotherapy interventions for the control of soil-transmitted helminthiases (STH) and schistosomiasis scaled up from a global coverage level of around 5% in the year 2000 to a coverage that surpassed 60% in the year 2019. The present paper analyses the concomitant reduction in the number of disability-adjusted life years (DALYs) lost due to STH and schistosomiasis during the same period, from 6.3 to 3.5 million DALYs. The cumulative gain during the 19-year period was estimated at over 26 million DALYs. Given the low cost of the intervention, our study suggests that deworming for STH and schistosomiasis is one of the most cost-effective public health interventions.